Mobile phone application to engage farmers and expand the reach of nutritious zinc-biofortified wheat in Pakistan - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The pilot, from October 2020-March 2021, is being co-implemented by HarvestPlus and Precision Agriculture for Development (PAD) and aims to test the strategy on 100,000 farmers.